2021
DOI: 10.1007/s00467-021-04990-4
|View full text |Cite
|
Sign up to set email alerts
|

APOL1 genotype-associated morphologic changes among patients with focal segmental glomerulosclerosis

Abstract: Background The G1 and G2 alleles of apolipoprotein L1 (APOL1) are common in the Black population and associated with increased risk of focal segmental glomerulosclerosis (FSGS). The molecular mechanisms linking APOL1 risk variants with FSGS are not clearly understood, and APOL1's natural absence in laboratory animals makes studying its pathobiology challenging. Methods In a cohort of 90 Black patients with either FSGS or minimal change disease (MCD) enrolled in the Nephrotic Syndrome Study Network (58% pediatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
(53 reference statements)
0
3
0
1
Order By: Relevance
“…APOL1 -associated FSGS is thought to be secondary to dose-dependent podocyte injury from the dominant toxic gain of function of the high risk APOL1 variants 12. Although APOL1- associated FSGS has been described mostly with two risk alleles, even a single risk allele is associated with cellular/tissue changes with some studies showing increased risk of chronic kidney disease with single G1 or G2 alleles 2 13–15…”
Section: Discussionmentioning
confidence: 99%
“…APOL1 -associated FSGS is thought to be secondary to dose-dependent podocyte injury from the dominant toxic gain of function of the high risk APOL1 variants 12. Although APOL1- associated FSGS has been described mostly with two risk alleles, even a single risk allele is associated with cellular/tissue changes with some studies showing increased risk of chronic kidney disease with single G1 or G2 alleles 2 13–15…”
Section: Discussionmentioning
confidence: 99%
“…A total of 476 (73%) underwent genetic testing, of whom 87 (18%) were at high risk, and it was found that highrisk APOL1 genotypes were the primary factor associated with faster loss of kidney function [15]. A cohort study of 90 black patients with FSGS or MCDs showed that while APOL1-associated FSGS is associated with having two risk alleles, both one and two risk alleles are associated with cellular/tissue changes in FSGS patients [16]. Expression of APOL1 risk variants in transgenic mouse models was found to increase susceptibility to lipid-dependent podocyte injury, ultimately leading to mitochondrial dysfunction [17].…”
Section: Genetic Testingmentioning
confidence: 99%
“…Additionally, APOL1 is associated with recurrent FSGS after transplantation [ 194 ]. Recently, Zee et al showed that glomerular APOL1 expression or APOL1 risk alleles are associated with cellular/tissue changes in patients with FSGS [ 195 , 196 ]. ApoL2 is found mainly in the brain [ 197 ], but its function remains unknown in the kidneys.…”
Section: Roles and Biological And Pathological Functions Of Apolipopr...mentioning
confidence: 99%